Work, burn, eat: abilities of calorimetric bodies in the USA, 1890–1930. Issue 2 (3rd April 2019) - Mackert, Nina
ABSTRACT: The article deals with calorimetric research around 1900 as an example of how the life sciences fundamentally contributed to ableism by creating blueprints of efficiently functioning human bodies as well as corresponding abilities that an individual had to have in order to be acknowledged as a subject and citizen. In the late 19th century, calorimetric research was part of broader efforts by physicists, physicians, chemists, and nutritionists to measure and maximize the workings and efficiency of human bodies. Laboratory experiments and broad dietary studies determined how much energy bodies needed to do work, how many calories different bodies burned at rest, and how people should eat. By determining metabolic regularities and ranking differently gendered, classed, and raced bodies according to their caloric needs, they established an intersectional metabolic able-bodiedness. Moreover, the calorie's suggestion that metabolic processes could be measured, regulated, and, thus, governed, created ways of eating 'right.' A short foray into early weight loss dieting shows how calorimetric science shaped a conceptualization of able citizens as those capable of properly budgeting their caloric intake in accordance with the needs of their bodies.